Balancing Pharmaceutical Innovation, Protection for Local Industries, and Potential Evergreening: An Analysis of Indonesia's Patent Law Amendments - Roisah, Kholis; Rahayu, Rahayu; Zaman, Muhamad Nafi Uz; Zainol, Zinatul Ashiqin; Mohd Zahir, Mohd Zamre (Universitas Negeri Semarang, 2025)
Recent changes to the Patent Law in Indonesia have sparked discussion regarding efforts to balance pharmaceutical innovation, protection of local industries, and the potential for evergreening practices. This study is a doctrinal research that uses a multi-approach analysis to examine the interaction between these variables in the context of Patent Law Number 65 of 2024. The study draws on literature reviews, theories and concepts related to drug patents, the pharmaceutical industry, the right to affordable medicine, and the evergreening. The research also includes an analysis of relevant laws and regulations, including the Patent Law before and after the amendment, to identify the changes and the underlying legal politics. The results show that the removal of Article 4 (f) of the Patent Law, which previously excluded certain inventions as inventions, may open up opportunities for the evergreening. However, the government argues that the deletion aims to protect local pharmaceutical companies and broaden the definition of invention. This study critically examines these claims, taking into account the readiness of the local pharmaceutical industry to compete with multinational corporations. In addition, there is a need for a strict control mechanism to ensure the validity of the invention in the patent as well as an objective evaluation of the inventive step and its therapeutic value. This study concludes that without adequate planning, the extension of patent protection to minor modifications may prolong commercial dominance of drugs, open opportunities for evergreening practices and ultimately hinder public access to essential and affordable drugs.